ANALYSIS OF MEDIA INFORMATION ABOUT ELIMINATION OF BREEDING PLACE - Indraswari, Ratih (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
Elimination of Breeding Place (EBP) is the most effective effort in preventing the occurrence of Dengue Hemorrhagic Fever (DHF). This effort has been socialized to the grassroot in order to be willing and able to conduct EBP routinely. Information on how to conduct EBP has often been exposed by using media communication. The use of media is expected to improve the understanding of the community so that the practice of EBP can be routinely implemented. This study aimed to determine the effect of media information on EBP toward the practice of EBP. This research used cross sectional approach. The sample in this study was 95 women obtained by simple random sampling technique. Most of the respondents were late adult (41.1%), graduated from primary school (30.5%), and housewives (67.4%). Respondents who practice EBP had supportive availability of media information (58.6%) than those with less information availability (32%). There is a relationship between information availability with the practice of EBP (p = 0.022). Women with less supportive media availability had a risk of 3.00 times not practicing EBP compared to women with supportive availability to media information (95% CI = 1,144-7,890). More respondents who practice EBP were in the group that had supportive availability of information (56%) than the less availability of information media (46.7%). Besides, this study indicated that there is no relationship between the accessibility of media information with the practice of EBP (p = 0.363). Availability of information media affects the practice of EBP. Women with less supportive information media availability had 3.00 times greater risk of not doing EBP. Meanwhile, the accessibility of media information about EBP has no effect on the practice of EBP in the community.